Eight Week Curriculum for Key Stage 1 Learners; Its Impact on the Improvement of their Academic Performance - ACOB, JOY L.; BRIGUEL, NERISSA A.; CARABLE, VENIS P; Dela Vega, Dan Evan; JALLORES, ELSIE R.; PAROLA, MANUEL A. (PT. BATARI EDU CALYA, 2023)
This study shows the 8 -week curriculum implementation for key stage 1 learners of the selected learners from Partido District, Division of Camarines Sur. It aims to know the impact of this intervention on the academic performance of the pupils in key stage 1. This study gathered information on how far the actual skills of the pupils with the expected skills for the grade level had been achieved. The result of the study shows that the reading performance level of the pupils varied from a full refresher, moderate refresher, light refresher, and grade level ready. Post-assessment results serve as the guiding star of the teachers on what step to take, what intervention to implement, and further instruction to do to be able to achieve the expected skills of the pupils in their grade level. Furthermore, the study shows how and what are the difficulties encountered by the teacher in implementing the 8-Week curriculum.